Molecular Assisted Identification Reveals Hidden Red Algae Diversity from the Burica Peninsula, Pacific Panama - Freshwater, David Wilson (2017)
The marine ﬂora of Panama harbors a rich diversity of green, red and brown algae,and despite chronic understudy, it is reported as the second most diverse marine ﬂora along thePaciﬁc Central American coast, with 174 macroalgal species. Extensive new collections and molecularassisted identiﬁcation (MAI) by an international team of researchers has revealed an even greaterdiversity for this country. Here, the intertidal and shallow subtidal marine ﬂora of the remoteBurica Peninsula is introduced. This area is characterized by an uplifted extensive intertidal ﬂatcomposed of ﬁrm, sedimentary benthos known as mudrock, on which abundant algal communitiesthrive, even during extended periods of exposure. A collection of nearly 200 brown, green and redmacroalgae specimens representing the ﬁrst marine ﬂoristic inventory of this region was made inJanuary 2011, and results of analyses of 45 foliose red algae specimens are presented. DNA sequencedata for several loci (rbcL-3P; COI-5P; UPA) have been generated for molecular assisted identiﬁcationand to guide morphological assessments. Twenty-six species were identiﬁed among the specimensincluding 21 new Paciﬁc Panama records, as well as previously unrealized transisthmian distributions,and two new species, Neorubra parvolacertoides sp. nov. and Grateloupia irregularis sp. nov